Black-Box for Blockchain Parameters Adjustment - Vladislav Amelin; Ernest Gatiyatullin; Nikita Romanov; Ratmir Samarkhanov; Robert Vasilyev; Yury Yanovich (IEEE Access, 2022)
This paper introduces a function for blockchain performance evaluation as a black-box. The function runs the Solana blockchain test network with the only differences between the main network in a configuration file and the physical network to operate in. The black-box takes setup parameters as input, launches blockchain in a cloud, emulates artificial users’ activity, and gives two outputs–transactions per second (tps) and drop rate. By default, the setup has six most important integer parameters and a network with three computers in the cloud, while one can vary eighty-nine parameters, the number of computers in the network and use local computers via black-box configuration files. The applied problem is to maximize the tps under a zero drop rate constraint. The black-box, like real blockchains, uses network communication, so reproducibility is an essential part of the design. We also provide an optimization baseline, showing the non-trivial results’ reachability.